Detection of vertical and horizontal crack in steel structure using a circular eddy current testing probe - Nurul A'in, Nadzri; Mohd Mawardi, Saari; Mohd Aufa Hadi Putera, Zaini; Zulkifly, Ab Aziz (American Institute of Physics, 2024)
Cracks in steel structures play a significant role in compromising the safety and reliability of facilities that incorporate steel, such as buildings, machinery, and bridges. Fractures may expand and result in complete breakage of the component, posing a significant risk to the life of the component and possibly resulting in injury or death. Fragile metal fractures occur with no apparent warning. The revelation of any cracks involves intensive steps to prevent them before they spread to the point of fracturing quality. The invention of an eddy current technique probe based on the investigation and extensive analysis of fluxgate sensors to investigate the presence of horizontal and vertical cracks in metal plates is presented in this paper. Two fluxgate sensors detect the magnetic response caused by the eddy current, which is generated by an excitation coil in the sample plates. The fluxgate probe is utilized to do line scans and 2-D map scans above the slits’ placements, and the results are classified to the depth of artificial slits. Using several frequencies and a 70-mA excitation current, the probe detected slits as small as 2 mm deep and 1 mm wide. The slit orientations perpendicular and parallel to the fluxgate sensors’ differential direction were observed, and their calculated lengths displayed a significant correlation with the physical gap lengths.